Observed parent–adolescent coalitions and family hostilities during family discussions: Associations with marital aggression. Issue 3 (7th September 2021) - Ramos, Michelle C.; Arbel, Reout; Timmons, Adela C.; Rodriguez, Aubrey J.; Margolin, Gayla
Abstract: This study investigated bidirectional associations between observed parent–youth coalitions—wherein one parent and a child align themselves against the other parent—and family hostilities as they evolved in real‐time during triadic family conflict discussions. Participants were 102 families with an adolescent child (50% girls, M age = 15.3 years, SD = 0.8). Using time‐lagged, multilevel models, we tested immediate, temporal influences from hostility (within marital and mother–youth and father–youth relationships) to parent–youth coalitions and vice versa. Guided by sensitization theories, we also investigated whether a history of marital aggression moderated these links. Results indicated multiple concurrent links supporting the interconnectedness of cross generational coalitions and angry, critical exchanges within multiple family relationships. Moreover, time‐linked effects demonstrated that hostility within both the marital and parent–adolescent domains preceded subsequent coalitions, and also that coalitions preceded hostility, particularly in the parent–adolescent domain. Findings further demonstrated that marital aggression moderates temporal associations between fathers' marital hostility and father–youth coalitions. These patterns highlight the dynamic links between hostilities and coalitions, how such patterns spill over across family subsystems, and how these two insidious influences in parents' interactions with their adolescent youth may mutually reinforce each other. This study informs intervention efforts by identifying patterns and sequences of family hostilities surrounding parent–youth coalitions during adolescence. Resumen: En este estudio se investigaron las asociaciones bidireccionales entre las alianzas observadas entre padres y adolescentes —en las cuales un padre y un hijo se alinean contra el otro padre— y las hostilidades familiares a medida que se desarrollaban en tiempo real durante discusiones triádicas por conflictos familiares. Los participantes fueron 102 familias con un hijo adolescente (el 50% niñas, edad promedio = 15.3 años, desviación típica = 0.8). Utilizando modelos multinivel con tiempo de retardo, evaluamos las influencias inmediatas y temporales de la hostilidad (dentro de las relaciones conyugales y de las relaciones entre madre y adolescente y padre y adolescente) en las alianzas entre padres y adolescentes y viceversa. Guiados por las teorías de sensibilización, también investigamos si los antecedentes de agresión conyugal moderaron estas asociaciones. Los resultados indicaron varias asociaciones simultáneas que respaldaron la interconexión de las alianzas intergeneracionales y los intercambios agresivos y críticos dentro de las relaciones de varias familias. Además, los efectos asociados con el tiempo demostraron que la hostilidad dentro del área conyugal y de padres y adolescentes precedió a alianzas posteriores, y también que las alianzas precedieron a la hostilidad, particularmente en el área de padres y adolescentes. Los resultados también demostraron que la agresión conyugal modera las asociaciones temporales entre la hostilidad conyugal de los padres y las alianzas entre los padres y los jóvenes. Estos patrones destacan las asociaciones dinámicas entre las hostilidades y las alianzas, las maneras en la que dichos patrones se desbordan entre los subsistemas familiares, y cómo estas dos influencias insidiosas en las interacciones de los padres con sus hijos adolescentes pueden reforzarse mutuamente. Este estudio sirve como base para los esfuerzos de intervención, ya que identifica los patrones y las secuencias de las hostilidades familiares que rodean a las alianzas entre los padres y los adolescentes durante la adolescencia.